Differences in Cardiac Magnetic Resonance Imaging Markers Between Patients With COVID-19-associated Myocardial Injury and Patients With Clinically Suspected Myocarditis. Issue 5 (September 2021) - Maurus, Stephan; Weckbach, Ludwig T.; Marschner, Constantin; Kunz, Wolfgang G.; Ricke, Jens; Kazmierczak, Philip M.; Bieber, Stephanie; Brado, Johannes; Kraechan, Angelina; Hellmuth, Johannes C.; Hausleiter, Joerg; Massberg, Steffen; et al.
Abstract : Purpose: Coronavirus 2019 disease (COVID-19) has been shown to affect the myocardium, resulting in a worse clinical outcome. In this registry study, we aimed to identify differences in cardiac magnetic resonance imaging (CMRI) between COVID-19 and all-cause myocarditis. Materials and Methods: We examined CMRI of patients with COVID-19 and elevated high-sensitivity serum troponin levels performed between March 31st and May 5th and compared them to CMRI of patients without SARS-CoV-2 infection with suspected myocarditis in the same time period. For this purpose, we evaluated Lake-Louise Criteria for myocarditis by determining nonischemic myocardial injury via T1-mapping, extracellular volume, late gadolinium enhancement, and myocardial edema (ME) by T2-mapping and fat-saturated T2w imaging (T2Q). Results: A total of 15 of 18 (89%) patients with COVID-19 had abnormal findings. The control group consisted of 18 individuals. There were significantly fewer individuals with COVID-19 who had increased T2 (5 vs. 10; P =0.038) and all-cause ME (7 vs. 15; P =0.015); thus, significantly fewer patients with COVID-19 fulfilled Lake-Louise Criteria (6 vs. 17; P <0.001). In contrast, nonischemic myocardial injury was not significantly different. In the COVID-19 group, indexed end-diastolic volume of the left ventricle showed a significant correlation to the extent of abnormal T1 ( R 2 =0.571; P =0.017) and extracellular volume ( R 2 =0.605; P =0.013) and absolute T1, T2, and T2Q ( R 2 =0.644; P =0.005, R 2 =0.513; P =0.035 and R 2 =0.629; P =0.038, respectively); in the control group, only extracellular volume showed a weak correlation ( R 2 =0.490; P =0.046). Conclusions: Cardiac involvement in COVID-19 seems to show less ME than all-cause myocarditis. Abnormal CMRI markers correlated to left ventricle dilation only in the COVID-19 group. Larger comparative studies are needed to verify our findings. Abstract : Supplemental Digital Content is available in the text.